Preventing β-Cell Loss and Diabetes With Calcium Channel Blockers - Guanlan Xu; Junqin Chen; Jing Gu; Anath Shalev (2012)
Although loss of functional β-cell mass is a hallmark of diabetes, no treatment approaches that halt this process are currently available. We recently identified thioredoxin-interacting protein (TXNIP) as an attractive target in this regard. Glucose and diabetes upregulate β-cell TXNIP expression, and TXNIP overexpression induces β-cell apoptosis. In contrast, genetic ablation of TXNIP promotes endogenous β-cell survival and prevents streptozotocin (STZ)- and obesity-induced diabetes. Finding an oral medication that could inhibit β-cell TXNIP expression would therefore represent a major breakthrough. We were surprised to discover that calcium channel blockers inhibited TXNIP expression in INS-1 cells and human islets and that orally administered verapamil reduced TXNIP expression and β-cell apoptosis, enhanced endogenous insulin levels, and rescued mice from STZ-induced diabetes. Verapamil also promoted β-cell survival and improved glucose homeostasis and insulin sensitivity in BTBR ob/ob mice. Our data further suggest that this verapamil-mediated TXNIP repression is conferred by reduction of intracellular calcium, inhibition of calcineurin signaling, and nuclear exclusion and decreased binding of carbohydrate response element–binding protein to the E-box repeat in the TXNIP promoter. Thus, for the first time, we have identified an oral medication that can inhibit proapoptotic β-cell TXNIP expression, enhance β-cell survival and function, and prevent and even improve overt diabetes.